The negative factors influencing the career intention of general practice trainees in eastern China: a qualitative study - Lei Tang (BMC Medical Education, 2022)
Abstract Background There is an acute shortage of general practitioners (GPs) in China, and GP trainees seem to be less willing to develop their career as a GP. This study aimed to investigate negative factors influencing the career intention of GPs in eastern China from the perspective of trainees taking standardized residency training, as to identify the barriers of GP trainees becoming registered GPs, and to provide a policy-making basis for GP recruitment and retention. Methods A qualitative description design by the purposive sample was carried out in two training bases of Jinan and Qingdao in eastern China. Face-to-face, in-depth, semi-structured interviews were conducted, audiotaped, and transcribed using thematic analysis. Results Twenty-one trainees participated in this study. Thematic analysis generated five major themes: (1) low social recognition, (2) low professional identity, (3) low remuneration level, (4) imperfect training system, and (5) influence of policy factors. Conclusions Our results identified various negative factors influencing the career intentions of trainees. In order to overcome the hurdles and increase the attractiveness of GP, it is recommended that the government and the public should create a supportive environment, which can be beneficial to the construction and development of GP.